The Application of Video-Based Learning Media with the Video Scribe Application to Improve the Learning Understanding of Grade IV Students in Social Studies Subjects at SDN Ciputat - Muparoha, Eva; Rahmawati , Tati; Latifah, Ulul (Jurnal Primagraha, 2023)
This study aims to find out 1) the application of Video Scribe learning media in social studies subjects for grade IV students of SDN Ciputat, 2) increasing student understanding in carrying out the learning process in social studies subjects for grade IV students of SDN Ciputat. The type of research used is qualitative descriptive. Qualitative data were obtained, among others, from interviews with teachers of social studies subjects for grade IV students of SDN Ciputat. This research design is a qualitative research that uses interview analysis. . Data collection techniques used in this study include: participatory observation, unstructured interviews, and documentation. Data analysis techniques used in this study include: data reduction, data presentation, verification / conclusions, and data collection. The results of this qualitative research 1) The learning media applied by the researcher is said to be successful with the acquisition of a score of 48 out of 50 by subject teachers who apply learning media to students. In addition, with the difference in the level of acquisition of observation guidelines obtained by researchers shows the level of difference in understanding shown by students who use learning media with students who are only taught by the lecture method, 2) Interesting learning media is able to increase student understanding of the learning process. This is because interesting learning media can attract students' attention so that students want to understand the material presented in the learning. The increase in understanding that students show between those who use media and those who do not use media is very different. This is also supported by the statement of social studies subject teachers that the learning media is successful in increasing student learning understanding when social studies lessons and the media is able to be applied in learning.